(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
The article analyzes the methodological foundations for improving the management of higher education institutions in the context of informatized education. Based on a review of scientific literature and existing theoretical approaches, the content of educational process modeling, the use of information and communication services, and their effectiveness are examined. The study substantiates the significance of the open structure of the pedagogical system, its interaction with the external environment, as well as the opportunities for interactivity, visualization, and the development of cognitive and creative skills in the educational process. Special attention is given to the role of information services as a methodological basis for enhancing the quality of education, strengthening students’ intellectual potential, and preparing competitive specialists in modern educational systems.